Stress in the workplace : studies of psychiatric nurses and prison service workers - Peacock, R. (Cranfield University, 1991)
Extensive depth interviews and self-completion questionnaires were used to assess subjective stress experience and issues relating to coping in samples of psychiatric nurses and prison service workers. Psychiatric nurses working within a psychiatric hospital due for closure had particular problems with stress relating to staff shortages, support from senior managers, and obtaining day-to-day resources. Four stress factors were elicited, the more important being related to staff shortages and support, and disputes. Enrolled Nurses and Staff Nurses, and nurses working within Continuing Care wards experienced the greatest problems with occupational stress in general. Comparative intra-role conflict and type A orientations to work were predictive of greater problems with occupational stress. Occupational stress was also a particular problem for dual careerists and nurses experiencing inter-role conflict. Low job satisfaction was related to greater problems with occupational stress. Prison service workers within a custodial establishment undergoing significant organisational change had particular problems with stress relating to paperwork systems, setting priorities, feelings of lack of appreciation from supervisors, inadequate feedback, and noise. Six stress factors were elicited, the more important being definition of work role, inmates, and setting priorities. Probation Officers experienced the greatest problems with occupational stress in general and the lowest levels of general psychological wellbeing as measured by a modified version of GHQ-12. Around one third of the sample experienced negative effects of stress in some area of their lives. Low job satisfaction was related to greater problems with occupational stress, and was predictive of low morale. Various factors regarding stress-related issues were assessed in terms of their predictive utility in determining basic grade prison officers' intentions to seek transfers and potential for leaving the service. The efficacy of presently used coping strategies and preferences for organisational coping resources were assessed for the two samples. Stress associated with role-related issues and significant events in the workplace are discussed. A model of stress is provided to account for stress in work settings - 'Stress in the workplace' - which defines stress in terms of ineffective coping with psychological demands. A variety of individual and organisational stress management / reduction strategies are reviewed. A general organisational framework for addressing stress in the workplace is provided in appended form.